Reuse of membrane filtered municipal wastewater for irrigating vegetable crops - Lopez A.; Pollice A.; Laera G.; Lonigro A.; Rubino P.; Passino R. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
In the framework of AQUATEC project, carried out in the period 2002-2006 in Southern Italy, a technical scale investigation was performed to test the suitability of membrane filtration for agricultural reuse of municipal wastewater. This membrane was tested on three different crops grown in rotation. Throughout the whole investigation, the quality of treated wastewater was monitored (chemically and microbiologically) and compared with conventional water pumped from a local freatic well. Both water sources were used in parallel for irrigating two separate plots of the test field. Except for higher Cl-, Na+ and B concentrations, the average chemical quality of tertiary filtered municipal wastewater was comparable with that of conventional well-water. Irrigation with treated wastewater caused an increase of Na+, Ca++ and EC values in the soil during summer periods that, however, were recovered during the following rainy seasons. From the microbial standpoint, unexpectedly, the plot irrigated with well-water resulted more contaminated than that irrigated with treated wastewater. The measured content of heavy metals in vegetables was independent of the water used for irrigation. Crops productivity did not show significant differences between the plot irrigated with treated wastewater and the one watered with well-water.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)